2022
DOI: 10.24996/ijs.2022.63.10.7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Investigation of Some Beta-lactamase Genes by PCR and DNA Sequencing Techniques in clinical Escherichia coli

Abstract: In this study, out of 50 isolates of some nosocomial infections from some Baghdad hospitals, only 13 (26%) were identified as Escherichia coli. Depending on selective media, morphological and biochemical tests the species was then confirmed by molecular methods. Later on  antimicrobial resistance test was performed by the Kirby-Bauer method. The molecular characterization of blaTEM and blaCTX-M genes in different clinical isolates of E. coli was done through polymerase chain reaction (PCR) by utilizing special… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
1
0
0
Order By: Relevance
“…Where there may be resistance genes other than those that have been studied that can confer resistance to the studied bacterial isolates. Bacteria may also develop mechanisms to reduce drug penetration into their cells, therefore E.coli has many mechanisms of resistance to βlactam antibiotics like loss of porin and efflux pumps [15][16][17]. The findings were agreed with other previous research which illustrated high resistance of E. coli to penicillin and most cephalosporins antibiotics [18] and agreements with other studies in low resistance to some antibiotics [19].…”
Section: Discussionsupporting
confidence: 90%
“…Where there may be resistance genes other than those that have been studied that can confer resistance to the studied bacterial isolates. Bacteria may also develop mechanisms to reduce drug penetration into their cells, therefore E.coli has many mechanisms of resistance to βlactam antibiotics like loss of porin and efflux pumps [15][16][17]. The findings were agreed with other previous research which illustrated high resistance of E. coli to penicillin and most cephalosporins antibiotics [18] and agreements with other studies in low resistance to some antibiotics [19].…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, ESBL producers were found to be rare in populations from Iran (21%) [ 9 ], Malaysia (24%) [ 25 ], Kermanshah, Iran (27.3%) [ 26 ], Saudi Arabia (23.1%) [ 27 ], Iraq (30.7%) [ 28 ], and only 6% in Libyans [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The E. coli isolates in this study were very resistant to ceftriaxone (81.7%), cefuroxime (81.7%), cefepime (100%), and ceftizoxime (90%) but not as resistant to meropenem (13.3%). Several studies have shown that E. coli isolates are resistant to many cephalosporines, such as cefotaxime, ceftriaxone, ceftizoxime, and cefepime [ 9 , 19 , 21 , 23 , 25 , 28 ]. However, other studies have shown that E. coli isolates are sensitive to meropenem [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation